Cardiovascular outcomes associated with concomitant use of clopidogrel and proton pump inhibitors in patients with acute coronary syndrome in Taiwan - Lin, Chen-Fang (Blackwell Science Inc, 2012)
AIMS: Our study aimed to examine the impact of concomitant use of proton pump inhibitors (PPIs) with clopidogrel on the cardiovascular outcomes of patients with acute coronary syndrome (ACS). Furthermore, we sought to quantify the effects of five individual PPIs when used concomitantly with clopidogrel. METHODS: We conducted a retrospective cohort study of patients who were newly hospitalized for ACS between 1 January 2006 and 31 December 2007 retrieved from the Taiwan National Health Insurance Research Database (NHIRD) and who were prescribed clopidogrel (n= 37 099) during the follow-up period. A propensity score technique was used to establish a matched cohort in 1:1 ratio (n= 5173 for each group). The primary clinical outcome was rehospitalization for ACS, while secondary outcomes were rehospitalization for percutaneous transluminal coronary angioplasty (PTCA) with stent, PTCA without stent and revascularization (PTCA or coronary artery bypass graft surgery) after the discharge date for the index ACS event. RESULTS: The adjusted hazard ratio of rehospitalization for ACS was 1.052 (95% confidence interval, 0.971–1.139; P= 0.214) in the propensity score matched cohort. Among all PPIs, only omeprazole was found to be statistically significantly associated with an increased risk of rehospitalization for ACS (adjusted hazard ratio, 1.226; 95% confidence interval, 1.066–1.410; P= 0.004). Concomitant use of esomeprazole, pantoprazole, rabeprazole and lansoprazole did not increase the risk. CONCLUSIONS: Our study indicated no statistically significant increase in the risk of rehospitalization for ACS due to concurrent use of clopidogrel and PPIs overall. Among individual PPIs, only omeprazole was found to be statistically significantly associated with increased risk of rehospitalization for ACS.